Intra-group trade credit and monetary policy: The case of China - Chou, Nan-Ting; Dai, Bingbin (Journal of Accounting, Business and Finance Research, 2026)
Using panel data from Chinese listed firms, this study investigates how monetary tightening and firm-specific characteristics influence trade credit received from different sources. The analysis categorizes trade credit into three groups: related parties, non-related parties, and controlling shareholders. The findings reveal that during periods of monetary tightening, Chinese firms receive more trade credit from related parties and less from non-related parties. This shift is particularly pronounced when the related party is a controlling shareholder. This asymmetry underscores the strategic importance of intra-group financing in mitigating liquidity constraints during monetary tightening. Furthermore, the impact of firm-specific characteristics on related-party trade credit differs markedly from their influence on non-related-party credit. These effects are more pronounced when controlling shareholders are the providers reflecting the unique dynamics of intra-group trust and reduced information asymmetry. The study sheds light on the distinctive mechanisms of corporate financing in China’s underdeveloped financial systems and advances the literature on the role of trade credit as a buffer during monetary contractions.